Bimetallic Ru‐Fe Nanoparticles Supported on Carbon Nanotubes for Ammonia Decomposition and Synthesis. Issue 4 (20th February 2020) - Chen, Cai; Chen, Yiwen; Ali, Arshid M.; Luo, Wenjia; Wen, Jie; Zhang, Lianhong; Zhang, Hui
Abstract: Alloy catalysts can achieve superior performance to single metal while reducing the cost by fine‐tuning the composition and morphology. Bimetallic Ru‐Fe nanoparticles were synthesized via liquid‐phase reduction method followed by impregnation with multiwall carbon nanotubes (CNTs) to prepare Ru‐Fe/CNTs catalysts. The Ru3 Fe/CNTs catalyst yields a superior catalytic stability for ammonia decomposition compared to the Ru/CNTs catalyst. Hence, the ammonia synthesis rate of the Ru3 Fe/CNTs catalyst was significantly higher than that of Ru/CNTs catalyst. The potential of bimetallic catalysts with reasonable composition and proportion will expand the research of efficient catalysts for ammonia decomposition and synthesis. Abstract : Monodispersed Ru and Ru3 Fe nanoparticles were prepared by liquid‐phase reduction followed by impregnation with multiwall carbon nanotubes (CNTs) to prepare Ru/CNTs or Ru3 Fe/CNTs catalysts. The synthesized Ru3 Fe/CNTs catalysts can effectively facilitate the synthesis and decomposition of ammonia and yield a superior catalytic stability for ammonia decomposition as compared to Ru/CNTs catalysts.